P107 Knowledge Of Non Invasive Ventilation In A District General Hospital – A Cause For Concern?. (10th November 2014) - Jones, RC; Stanton, A; Juniper, M
Abstract : Introduction: Non Invasive Ventilation (NIV) is being used more widely in acute areas by medical staff with varied training and experience in initiation and ongoing management of ventilatory failure. Aims: To investigate doctors' knowledge of NIV in an emergency department (ED) and general medical wards, specifically indications for use, appropriate set up and ongoing care. Methods: An anonymous online and written questionnaire was distributed to all doctors working in general medicine and in the ED at a UK district general hospital in Spring 2014. Participants were asked to identify appropriate indications for NIV and then led through a scenario of managing a patient with COPD and decompensated ventilatory failure. Results: 40/116 (34%) of doctors responded across all grades. On a 6-point scale. self-identified confidence in managing NIV improves with seniority (5.2 (ST3+) vs 3.3 (FY1-ST2)) and past job experience in ICU (4.1 vs 3.6). Doctors were unclear about indications for NIV outside ICU/HDU. Whilst the majority (95%) correctly identified COPD exacerbations as an indicator, doctors at all grades would also use NIV for: asthma (10%), significant hypoxia (10%) and pneumothorax (3%). A fifth (18%) would start NIV without initial medical therapy. Only 55% (22/40) could identify appropriate initial ventilatory pressures (initial IPAP range 4–16, initial EPAP range 4–16). Suggesting a value for back up rate was more problematic with 43% (17/40) unable to provide any value and 9/23 (39%) suggesting an inappropriate value (range 8–18). Only 55% (22/40) could correctly alter settings while 23% (9/40) of doctors altered both IPAP and EPAP by equal amounts. 50% (4/8) ED/medical registrars could not alter settings correctly Conclusions: Knowledge of appropriate use of NIV is sub optimal across all grades working in the ED and general medicine in our institution, and probably reflects the increasing use of a specialist intervention in the hands of non-specialists. There are a number of doctors whose use of NIV could compromise patient safety. Urgent education across all grades is needed alongside review of how NIV is delivered in the DGH setting.